Effect of Harvest Maturity and Variety on Yield And Nutritional Quality of Squash in Bangladesh - Hossen, Md Afzal; Islam, Md Nazrul; Akther, Shamima; or Rashid, Mohammed Harun; Sabuz, Ashfak Ahmed; Amin, Md Al (Bangladesh Journal of Agriculture, 2025)
Squash (Cucurbita pepo L.) yield can vary significantly depending on harvesting date. To overcome this issue, a field experiment was conducted at the Vegetable Research field of Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh, during October 2019 to March 2020 to find out the effect of variety and harvesting date on yield and yield attributes of squash. The experiment comprised two sets of treatments viz., (A) Variety: (i) BARI squash1 (V ) and (ii) Kajol-F 1 1 2(V) and (B) Harvesting date: (i) 5 days after fruit setting (H ); (ii) 10 days after fruit setting (H ); (iii) 1 2 15 days after fruit setting (H ); (iv) 20 days after fruit setting (H ) and (v) 25 days after 3 4 fruit setting (H ) in a Randomized Complete Block Design (RCBD) with three replications. 5 The results showed that the variety BARI squash1 showed significantly the highest number of fruit plant, fruit length, yield and vitamin C content, five days after fruit setting showed -1 significantly the highest fruit plantand vitamin C content but the highest yield plantand -1 -1 yield hawere found from 20 days after fruit setting. The interaction between variety and -1 harvesting date was significant for yield and quality parameters except moisture (%). Based on the study results it is concluded that maximum yield plant(4350 g) and yield (43.30 t -1 ha ) were recorded from BARI squash1 with 20 days after fruit setting, but higher TSS -1 and vitamin C was found in BARI squash1 where crop harvested 5 days after fruit setting. Variety BARI squash1 harvesting at 20 days after fruit setting (V H ) is sutable for higher 14 yield and Variety BARI squash1 harvesting at 5 days after fruit setting (V H ) is sutable 11 for higher nutritional quality of squash in Bangladesh. Bangladesh J. Agri. 2025, 50(1): 95-105